Ageing, work-related stress and health: reviewing the evidence - Griffiths, Amanda; Knight, Alec; Mohd Mahudin, Nor Diana (Age UK/The Age and Employment Network, 2009)
This scientific literature review was jointly commissioned by TAEN - The Age and Employment Network, and Age Concern and Help the Aged. The majority of of reviews of research on work-related stress, its causes and its effects have been based on large groups of workers very rarely distinguished by age. This report addresses this gap. The review found that stress levels peak at about 50 to 55 years of age and decrease towards retirement. The effects of work-related stress can last well into retirement.